FILM ANIMASI ‘RIKO THE SERIES: EPISODE TANAMAN BERTASBIH’ (Kajian Living Qur`an) - Muhammad Taufiq; Ahmad Mustofa (Wahana Islamika Jurnal Studi Keislaman, 2023)
This article intends to identify the form of the reception of the Qur'an contained in the 20th episode of the animated film Riko The Series entitled "Tanaman Bertasbih". This episode aired on the YouTube channel and received a positive response from its viewers who had reached 3,941,335 views. This study uses the theory of al-Qur'an reception which was popularized by Ahmad Rafiq. The results of this study indicate that the animated film Riko The Series is an animated film that contains educational, creative and Islamic content that also accepts the Qur'an in it. There are two forms of reception in this episode entitled “Tanaman Bertasbih”, namely exegesis reception, namely QS. al-Isra verse 44, and functional reception in the informative aspect, namely as a guide for humans to respect and respect all living things, especially plants which according to scientific evidence always glorify and praise Allah.